The importance of the English language in the community tourism at the touristic route of Isinlivi, Chugchilan and Quilotoa, AIMED to local people. - Enríquez Moya, Marcial Augusto (2018)
The present research work was carried out in order to know the importance of the English language in the community tourism at the tourist route of Isinliví, Chugchilan and Quilotoa belonging to Cotopaxi province within Sigchos and Pujili cantons; which is focused for the local people since the people of this sector do not speak the English language due to lack of interest, motivation and practical resources that boost the spirit to learn this language.It has seen that in the last 30 years, the touristic sector has quickly developed in all Ecuador, also in Cotopaxi province, and in special, in this touristic route due to the wonderful landscape and its geographical contrast capturing national and international tourists´ attention. For this purpose, it was proposed as an objective: To determine the importance of communicating in the English language with foreign tourists in order to improve the community tourism at the touristic route of Isinlivi, Chugchilan and Quilotoa.So, it was also obtained a lot of information using the descriptive, deductive and inductive methods with data collecting instruments such as: surveys and interviews. The actual information existing in a few historical books, magazines and the technological instruments played an important aspect and even, the researcher´s autonomous knowledge took into account and hisown experience to reinforce the practical researching and realize the existing problem.Many methodological processes had been used in the Teaching and learning process of the English language but, they have not effectively reached to all educational institutions of this touristic sector and people have downplayed the importance of using this language. So it is advisable to use some strategies and techniques which are supported in this research the same that will help to develop the skills to learn this language. Finally,it is urgent to encourage the interest to learn the English language by means of usingpractical resources such as: English books and magazines, Audio-visual videos, Media, Internet, foreign volunteers who can work in the educative institutions, the creation a touristic English guide brochure with specific information to promote the community tourism in this zone since local people don´t speak English.Otherwise, it´s possible to have for many more years the same social and traditional situation in terms of guiding local tourism and it might possibly miss the chance of taking advantages and learning something more about the English culture and this beautiful route.